Systematics in the Cepheid and TRGB Distance Scales: Metallicity Sensitivity of the Wesenheit Leavitt Law - Barry F. Madore; Wendy L. Freedman (The Astrophysical Journal, 2024)
Using an updated and significantly augmented sample of Cepheid and tip of the red giant branch (TRGB) distances to 28 nearby spiral and irregular galaxies, covering a wide range of metallicities, we have searched for evidence of a correlation of the zero-point of the Cepheid period–luminosity relation with H ii region (gas-phase) metallicities. Our analysis, for the 21 galaxies closer than 12.5 Mpc, results in the following conclusions: (1) The zero-points of the Cepheid and TRGB distance scales are in remarkably good agreement, with the mean offset in the zero-points of the most nearby distance-selected sample being close to zero, Δ μ _o (Cepheid—TRGB) = −0.026 ± 0.015 mag (for an I -band TRGB zero-point of M _I = −4.05 mag); however, for the more distant sample, there is a larger offset between the two distance scales, amounting to −0.073 ± 0.057 mag 〈Δ μ _o 〉 (Cepheids—TRGB) = −0.026 ± 0.015 mag, for an I -band TRGB zero-point of M _I = −4.05 mag. (2) The individual differences, about that mean, have a measured scatter of ±0.068 mag. (3) We find no statistically significant evidence for a metallicity dependence in the Cepheid distance scale using the reddening-free W ( V , VI ) period–luminosity relation: Δ μ _o ( Cepheid − TRGB ) = − 0.022( ± 0.015) × ([O/H] − 8.50) − 0.003(±0.007).